2015
DOI: 10.1016/j.ydbio.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Time course for tail regression during metamorphosis of the ascidian Ciona intestinalis

Abstract: In most ascidians, the tadpole-like swimming larvae dramatically change their body-plans during metamorphosis and develop into sessile adults. The mechanisms of ascidian metamorphosis have been researched and debated for many years. Until now information on the detailed time course of the initiation and completion of each metamorphic event has not been described. One dramatic and important event in ascidian metamorphosis is tail regression, in which ascidian larvae lose their tails to adjust themselves to sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 56 publications
2
35
1
Order By: Relevance
“…2 The duration of larval swimming differs among individuals. Matsunobu et al (2015) showed that the hatched larva requires at least three or four hours to get competence to commence metamorphosis. So the time after fertilization during Larva Period was broad.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The duration of larval swimming differs among individuals. Matsunobu et al (2015) showed that the hatched larva requires at least three or four hours to get competence to commence metamorphosis. So the time after fertilization during Larva Period was broad.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that, in annotating the progressive organ appearance and degeneration, we could also describe in detail the metamorphosis process, whose general reports for ascidians are dated, not so accurate and timed, and limited to a few species (see for review: 29,41 ). Only some specific processes occurring during metamorphoses, such as tail regression 39,42 or papillae retraction 42 , have been described in detail in C. robusta.…”
Section: Discussionmentioning
confidence: 99%
“…When the larvae started adhesion, the seawater of the petri dishes was exchanged several times to remove any unsettled larvae. This treatment was done to synchronize the timing of metamorphosis (Matsunobu and Sasakura, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that, in annotating the progressive organ appearance and degeneration, we could also describe in detail the metamorphosis process, whose general reports for ascidians are dated, not so accurate and timed, and limited to a few species (see for review: 29,41 ). Only some specific processes occurring during metamorphoses, such as tail regression 39,42 or papillae retraction 42 , have been described in detail in C. robusta (C. intestinalis type A).…”
Section: The Developmental Ontologymentioning
confidence: 99%